Distribution and correlates of high waist-hip ratio in adults in selected rural areas in Sto. Tomas, Batangas - Alicante-Duante, Charmaine
The waist-hip ratio (WHR), a simple indicator of abdominal obesity has been found to be closely related with metabolic abnormalities like CVD, stroke, NIDDM and other risk factors to CVD in both cross-sectional and longitudinal studies. Because of the scarcity of information on this anthropometric measure in the country, a need was felt to study this indicator in the Philippine setting. The distribution of WHR and correlates of a high WHR and correlates of a high WHR were investigated among adults aged 30-60 years in four selected rural areas in Sto. Tomas, Batangas. A total of four hundred ninety one (491) men and seven hundred thirty nine (739) women were studied with the exclusion of pregnant women. The distribution of study participants by WHR and the different categories of independent variables related to WHR were described as symmetrical. Among obese, overweight and sedentary male individuals, the distributions could be described as skewed to the left which showed that greater proportions of these group of individuals were found to be with high WHR values. Findings of this study showed that abdominal obesity was present in the study population. Another important clinical findings of this study was the higher prevalence of overweight and obesity in the study population. Using the recommended WHR cut-off point of equal to or more than 0.91 for males and equal to or more than 0.81 for females, 64.2 of males and 71.2 of females were found to be with high WHR. It was also shown in this study that the prevalence of high WHR was significantly higher among females than males. Several factors were found to be related with a high WHR. Among males, age, educational level and total obesity as measured by BMI were found to be significant correlates of a high WHR. As the males get older, the risk of having WHR becomes greater. Educational level behaved in contrary to the findings of many that WHR is inversely proportional to the level of education. Moreover, the risk of having high WHR among those who were overweight and obese was 4.2 than those who were of normal BMI. Smoking status alone did not contribute in an increase in WHR, however, the risk of having high WHR was 12.6 times higher among overweight and obese smokers than those who were not overweight nor obese and at the same time not a smoker. On the other hand, factors related to a high WHR among females were age, civil status and BMI. Females as they grow older, the WHR becomes low.